Fetal blood vessel count increases in compensation of hypoxia in premature placentas - K Kartini; Ahmad A Jusuf; Sri Widia A Jusman; M Ekawati; Ani R Prijanti (Universa Medicina, 2015)
BACKGROUND Prematurity refers to live births before 37 weeks of gestation, wherein the baby is born before the body and its organ systems achieve perfect maturity, and this disorder is still a global problem. The high incidence of prematurity is a problem in developing and also in developed countries. Certain conditions accompanying pregnancies like preeclampsia, infection, and placental insufficiency, may trigger uterine hypoxia, causing premature birth. The placental condition is related to the intra-uterine fetal condition. In prolonged placental hypoxia, there occurs a compensatory mechanism, i.e. an increase in placental angiogenesis. This study aimed to evaluate the effect of hypoxia on fetal blood vessel count as compensatory mechanism for tissue hypoxia. METHODS An observational-analytical cross-sectional design using paraffin blocks of conserved premature placentas, comprising 31 samples of hypoxic premature placentas and 28 samples of non-hypoxic premature placentas, selected using non-random consecutive sampling. The samples were made into slides and stained with hematoxylin-eosin for assessment of histological structure, including fetal blood vessel count and integrity, villus conditions, syncytiotrophoblastic nuclear changes, and syncytiotrophoblastic nuclear aggregation. Mann-Whitney test was used to compare the difference of blood vessel count between groups. RESULTS Assessment of histological structure showed a significant increase in fetal blood vessel count in the hypoxic group [8.00 (5-15)] as compared with the non-hypoxic group [7.50 (3-15)]. CONCLUSION The hypoxia in premature placentas caused an increase in the number of fetal blood vessels as a form of compensation for disturbed oxygen homeostasis.